Pemanfaatan Canva Sebagai Media Perancangan Grafis - Supradaka Supradaka (IKRAITH-Teknologi, 2022)
Canva is an online design application that provides various tools or editing tools to easilycreate various graphic designs without the need to design them from scratch. This research is intendedto provide solutions for using Canva application as a graphic design medium for novice designers andonline marketers. This study uses an innovation diffusion theory approach which examines thedissemination process and the adoption process that occurs in society towards the presence of a newinnovation. This study uses a qualitative descriptive approach to interpret the existing phenomena. Theprimary data collection process was carried out through in-depth interviews. The results of this studydescribe that the use of Canva as a graphic design medium is able to provide convenience in its use,increase creativity and produce graphic design content with new innovations